ANALISIS PENATAUSAHAAN ASET TETAP DAERAH BERDASARKAN PERMENDAGRI NOMOR 19 TAHUN 2016 PADA BIRO UMUM SEKRETARIAT DAERAH PROVINSI SULAWESI TENGGARA - Nurul Annisa; Abdul Aziz Muthalib; Nita Hasnita (STIE ENAM ENAM KENDARI, 2022)
This research intends to find out and analyze the administration of regional fixed asset according to the Regulation of the Minister of Home Affairs No. 19 of 2016 in the Regional Secretariat General Bureau of South East Sulawesi. It used a qualitative descriptive approach. It also used document observation, interviews, and literature study as data collection techniques. The result indicated that the administration of regional fixed assets in the Regional Secretariat General Bureau of South East Sulawesi in terms of the indicators of bookkeeping, inventory, and reports had followed the management provision stated in the Regulation of the Minister of Home Affairs No. 19 of 2016, in which the General Bureau Chief through Consumer Goods Administrator had regularly conducted registration and recording activities of regional fixed assets in consonance with the goods classification and codification, conducted the inventory of regional fixed assets by inventory team once in five years or every year for fixed assets namely construction in execution, and making semestrial and annual goods realization statements which were routinely reported to Regional Secretary of South East Sulawesi through Head of Asset Section in Office of Management or Regional Revenue, Finance, and Assets (BPKAD) of South East Sulawesi